2018
DOI: 10.5897/jene2018.0709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use and land cover changes on ecosystem services in the Bilate Alaba Sub-watershed, Southern Ethiopia

Abstract: Human well-being was obsessed with the natural scheme that provides various functions vital to support management at various levels. Land use/ land cover (LULC) dynamics over 45 years within four intervals (1972, 1986, 2008, and 2017) to evaluate its influence on ecosystem services. Geographic information system (GIS) and global value of coefficients' database together with LULC dynamics were used to determine ecosystem service values (ESV). The results showed that cultivated land and settlement land expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…Tefera and Sterk [ 25 ] reported that croplands were endlessly expanding from comparatively flat areas in 1957 and 1980 to steep lands in 2001 at the expense of grazing lands, which are found in Fincha watershed, western highlands of Ethiopia. Markos and colleagues [ 26 ] showed that cultivated lands and settlement land expanded by 67.4 and 532%, respectively, whereas forest land and shrubland and grassland declined by 66.4 and 18.4%, respectively, over the analysis period. Expansion of agriculture in Ethiopia is related to a change in land use policy with a change of regimes from Derg to Ethiopian People Revolutionary Democratic Front [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tefera and Sterk [ 25 ] reported that croplands were endlessly expanding from comparatively flat areas in 1957 and 1980 to steep lands in 2001 at the expense of grazing lands, which are found in Fincha watershed, western highlands of Ethiopia. Markos and colleagues [ 26 ] showed that cultivated lands and settlement land expanded by 67.4 and 532%, respectively, whereas forest land and shrubland and grassland declined by 66.4 and 18.4%, respectively, over the analysis period. Expansion of agriculture in Ethiopia is related to a change in land use policy with a change of regimes from Derg to Ethiopian People Revolutionary Democratic Front [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the approach proposed by Costanza et al [ 43 ], we calculated the ESVs per unit area for each LULC class based on ESVD value coefficients ( Table 3 ; Table 4 ). Some land use classes, such as bare land and built-up areas, did not have coefficients in previous studies [ 4 , 12 , [19] , [20] , [21] , [23] , [24] , [25] , [26] , [27] ]. Likewise, in our study, no coefficients were assigned to bare land, built-up, and burned areas.…”
Section: Methodsmentioning
confidence: 85%
“…Therefore, assessing the services provided by different ecosystems and quantifying their spatial and temporal changes is crucial for the efficient management of social-ecological systems [ 22 ]. In Ethiopia, only few studies have been carried out by quantifying the impacts of LULC dynamics on ecosystem services [ 4 , 12 , [19] , [20] , [21] , [23] , [24] , [25] , [26] , [27] ]. These studies were mainly confined to forest ecosystems of Ethiopian highlands [ 4 , 12 , 21 , 23 ], watersheds and basins [ [24] , [25] , [26] ], and agroforestry dominated landscapes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e Ethiopian People Revolutionary Democratic Front (EPRDF) sustained the same land policy that encouraged smallholders to put extra forest area into cultivation to produce high-value crops for possible markets and agro-processing plants favoring a mixed economy [25].…”
Section: Discussionmentioning
confidence: 99%